Growth, maturation and development during childhood and adolescence: Implications for sports practice - Alessandro H. Nicolai Ré (Desafio Singular, 2011)
Human development emerges from the interactions between environmental and biological factors. This review focuses on the relationship between biological development and environmental experiences during infancy and adolescence and their implications for motor skill acquisition. During infancy, as a consequence of the accelerated development of the central nervous system, it is fundamental that a vast and adequate variation in environmental stimuli is supplied, favoring motor, cognitive and affective-social domains. In adolescence, biological alterations are associated with peaking testosterone and estradiol hormone production in males and females respectively and it is necessary to adjust motor stimulation to biological maturation and previous experiences. Motor skill acquisition during infancy has an important relation to continuity of physical activity in later years and the practice of sports in adolescence and adulthood, favoring both the blossoming of athletes and promotion of health in general population.